The effects of glucose and fructose on body weight and some biochemical parameters in rats - Köseler, Esra; Kızıltan Gül; Türker Perim Fatma; Saka, Mendane; Akçil Ok, Mehtap; Bacanlı, Didem; Aydos, Tolga Reşat; Bayraktar Nilüfer; Özdemir, Handan (Progress in Nutrition, 2018)
Objective: Dietary fructose from added sugar as high fructose corn syrup may causes major risks in obesity, hyperlipidemia, cardiovascular diseases, hyperuricemia and fatty liver. The aim of this study was to investigate and compare the effects of high fructose and high glucose intake on body weight and some biochemical parameters in rats. Subject and methods: The study was conducted on adult, 32 Wistar albino male rats (300-350 g weeks) which fed with standard laboratory chow. In each group, 8 rats was selected randomly and which was be composed four groups. The rats in each group, in addition to standard meal, different amount of glucose and fructose containing solutions (10% and 30% glucose-fed group, 10% and 30% fructose-fed group) was given by oral gavage for 6 weeks. At baseline and after 6 weeks total cholesterol, VLDL-cholesterol, triglycerides, uric acid, AST and ALT as biochemical parameters and liver histopathological examination of rats were determined. Body weight of the rats was evaluated every week. Results:The 30% fructose group caused higher AST levels according to 10% glucose group, 30% glucose group and 10% fructose group. At the end of 6 weeks, the mean body weight in the fructose-fed groups was higher than the glucose-fed groups (p>0.05). No statistically significant difference between rat groups’ portal inflammation rates were found and the moderate and severe ballooning were observed in 30% fructose rats (p<0.05). Conclusions: As a result, dietary fructose from added sugar as high fructose corn syrup may causes major metabolic disorders.